THE ROLE OF THE NURSE IN THE CARE OF PATIENTS WITH AUTISM SPECTRUM DISORDER (REMUNOM, 2026)
This article aimed to analyze the importance of the nurse’s role in supporting the paternal figure of children with Autism Spectrum Disorder (ASD), considering the impacts of the diagnosis on family dynamics and the relevance of humanized, family-centered care. This is an integrative literature review carried out through the analysis of scientific articles published in health-related journals. The selected studies showed that the diagnosis of ASD significantly affects the life of the paternal figure, producing emotional, social, and organizational impacts that require welcoming, guidance, and professional support. In this context, the nurse plays a fundamental role by promoting qualified listening, health education, strengthening the bond with the family, and including the father in the child’s therapeutic process. Educational actions developed with the family and the multidisciplinary team are also highlighted, as well as the importance of early identification of family needs and comprehensive care. It is concluded that the nurse plays a strategic role in supporting the paternal figure of children with ASD, contributing to more inclusive, humanized, and family-sensitive care.